Bioinformatics : sequence,structure and databanks: a practical approach - Higgins, Des ( Editor); Taylor, Willie. ( Editor) (Oxford : Oxford University Press, 2001)
Bioinformatics is concerned with the use and organisation of biological information using computer databases and integrating it with data from other sources.
Keywords: Biology -- Data processing; Proteins; Molecular biology